HUBUNGAN HUKUM ANTARA PERUSAHAAN PENYEDIA JASA DENGAN PERUSAHAAN PENERIMA JASA - Manik Muantari Suantari Sri Utami, Ni Luh; Oka Parwata, Anak Agung Gede (Kertha Semaya : Journal Ilmu Hukum, 2013)
Relationship between service providers and service recipients very close when service providers company provide labor services to service recipients company and remuneration paid as agreement of both parties. Laborers can do outside of the principal work except directly related activities with production process. Use normative method sourced on primary law nor secondary and regulatory legislation.
Keywords: Relationship , Laborers, Company, Responsibility